Comparing the Results of Chest X-ray with Chest Ultrasound in Neonates Admitted in Neonatal Intensive Care Unit - Elham Zarei; Vahid Alizadeh (JCDR Research and Publications Pvt. Ltd., 2018)
Introduction: Chest X-ray (CXR) is the potential method for the diagnosis of pulmonary disorders. It has been using in respiratory distress syndrome detection in neonates. Aim: To compare the diagnostic accuracy of lung sonography against the CXR in Acute Respiratory Distress Syndrome (ARDS) in newborn babies admitted in Neonatal Intensive Care Unit (NICU). Materials and Methods: This cross-sectional study was conducted on newborns admitted in NICU ward during July 2016 to April 2017. The recorded data includes gender, gestational age at birth and bedside trans-thoracic chest ultrasonography from the neonates, which were undergone anterior-posterior CXR by the clinical physician. The chest sonography was accomplished longitudinally from anterior and lateral chest. Two different expert radiologists performed the interpretation of CXR and sonography without knowledge about the results of other test. Results: Total 134 newborns were enrolled in this study containing 75 males (55.9%). Seven cases had congenital abnormality including diaphragmatic hernia and situs inversus. Pneumothorax and pleural effusion were detected in eight and four cases, respectively. All these diagnoses were confirmed by both CXR and chest sonography. The most prevalent findings in CXR were haziness and consolidation. Chest sonography showed abnormal pleural line in 55 newborns (41%), more than three B-lines in 44 cases (32.8%), white lung in 31 newborns (23.1%) and consolidation in 38 patients (8.4%). Chest ultrasonography had 89.09% (95% CI, 81.72%-94.23%) sensitivity and 95% (95% CI, 75.13%- 99.87%) specificity for diagnosis of chest abnormalities in NICU-admitted neonates. Conclusion: Although, sonography has good potential for diagnosis of chest pathologies in newborns, it seems it is not the first step for assessing the newborns' chest, instead of CXR. However, chest sonography is so valuable for serial follow-ups and as a supplementary technique in suspicious CXRs.